1985
DOI: 10.1111/j.1348-0421.1985.tb00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Effect of Gram‐Positive Bacteria vs. Gram‐Negative Bacteria on Adjuvant‐Induced Arthritis in Germfree Rats

Abstract: Germfree (GF) F344 rats developed severe adjuvant-induced arthritis with a 100% incidence after a single intradermal injection of heat-killed Mycobacter i u m bovis (BCG). Specific pathogene-free (SPF) rats developed less severe arthritis with a lower incidence. The rats colonized with Escherichia coli or Bacteroides developed mild disease comparable to that in SPF rats. The rats colonized with Bifidobacteri u m, Propionibacterium acnes, Lactobacillus casei, L. fermentum, L. murini, and L. acidophil u s develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Using animal models of experimental colitis [34] and arthritis [35] it was shown that Gram-negative bacteria, possibly through the TLR2/IL-10 axis, reduced inflammation [34], whereas Gram-positive bacteria contributed to a more severe disease [35]. In a mouse model of Sjögren’s disease, depletion of the intestinal microbiome worsened the ocular response to desiccation, while the overall severity of disease correlated with intestinal microbiome diversity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Using animal models of experimental colitis [34] and arthritis [35] it was shown that Gram-negative bacteria, possibly through the TLR2/IL-10 axis, reduced inflammation [34], whereas Gram-positive bacteria contributed to a more severe disease [35]. In a mouse model of Sjögren’s disease, depletion of the intestinal microbiome worsened the ocular response to desiccation, while the overall severity of disease correlated with intestinal microbiome diversity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Such a hypothesis would not exclude a role for other bacterial genera such as Proteus. It is known that the ability of BCG to evoke adjuvant arthritis in germ-free rats can be increased or decreased by prior reconstitution of the bowel flora with various bacterial species [12]. Therefore it may be the dose and sequence of exposure to different variants of the 65 kDa gene family which determines whether the primed T cells resemble the arthritogenic or suppressor inducer clones identified in AA [30].…”
Section: Do Mycobacteria Play a Special Role In The Aetiology Of Ra?mentioning
confidence: 99%
“…If such is indeed the case, then it would be interesting to study T cell subpopulations in SPF rats after stimulation of BCG or MDP. Our previous findings that gram-negative bacteria such as Escherichia coli suppressed the disease in GF F344 rats, whereas gram-positive bacteria, such as Lactobacillus casei, enhanced development of the disease (11)(12)(13), provide an insight into the important role of microbial flora in modulating development of adjuvant disease by regulating T cell subpopulations. Our study showed that thymus or T cell functions play a primary role in producing adjuvant disease and microbial flora plays a secondary role in modulating the disease and the epithelioid granuloma formation, through yet to be determined mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that GF F344 rats developed a more severe form of the disease than did SPF and CV F344 rats and also that gram-negative bacteria suppressed the disease, whereas gram-positive bacteria enhanced the disease. We suggested that microbial flora may play an important role in modulating development of the disease (11)(12)(13) . Congenitally athymic nude SFP rats did not develop adjuvant arthritis but did have an immature epithelioid granuloma which matured when reconstituted with thymus or spleen cells from thymus bearing littermate (rnu/ +rats) (20) .…”
mentioning
confidence: 99%